Serum concentration and kidney expression of salusin-? and salusin-? in rats with metabolic syndrome induced by fructose - Sahin, I.; Aydin, S. (Taylor & Francis Ltd, 2013)
Salusins expressed in a variety of tissues exert a hypotensive effect owing to their vasodilator action. They are found in serum and tissues in two different forms: salusin-alpha and salusin-beta. Metabolic syndrome (MetS) is an important public health problem characterized by diabetes, obesity, abnormal blood lipid levels and high blood pressure. We investigated how salusins in the circulation and in kidney tissues change in relation to MetS. Experiments were conducted on 5-week-old Sprague-Dawley male rats assigned to either a control group or a MetS group. Controls were fed standard rat food and water ad libitum, while the MetS group was fed standard food with 10% fructose solution added to their drinking water for three months. After three months, all animals were sacrificed after a one night fast. Blood and tissues were collected and stored appropriately. Biochemical parameters were analyzed using the Konelab 60 auto-analyzer. Salusin-alpha and salusin-beta levels in the blood and kidneys were studied using the ELISA method. The salusin expression in the renal tissue was shown by immunohistochemical staining. Compared to the control group, the MetS group showed elevated uric acid and other lipid parameters for high-density lipoprotein cholesterol. Serum salusin-alpha and salusin-beta levels were decreased; however, salusin levels/mg kidney tissue were elevated. Immunohistochemical analysis of salusins in kidney tissue revealed their presence in the epithelium cells of the glomeruli, and proximal and distal tubule cells. The expression of both peptides in renal tissues was greater in the MetS group than in the control group. We believe that salusins are critical mediators in the etiopathology of MetS. Altered salusin levels are thought to regulate hypertension, which is a component of MetS.
Keywords: immunohistochemistry; kidney; metabolic syndrome; salusins